Risk factors of incident type 2-diabetes mellitus over a 3-year follow-up: Results from a large Australian sample. Issue 2 (May 2015) - Ding, Ding; Chong, Shanley; Jalaludin, Bin; Comino, Elizabeth; Bauman, Adrian E.
Abstract Aims To describe the incidence of type 2 diabetes mellitus (T2DM) among middle-aged and older Australian adults and to examine a broad range of risk factors of T2DM. Methods A large cohort of Australian adults aged 45 and up was sampled from the general population and was followed up for approximately 3 years (n = 60, 404). Physician-diagnosed T2DM was self-reported at baseline (2006–2008) and follow-up (2010). Incident T2DM was determined as not reporting T2DM at baseline, but reporting T2DM at follow-up. A broad range of risk factors, including socio-demographic characteristics, health status, family history, and lifestyle behaviors were examined at baseline. Multiple logistic regression was used for selecting potential predictors of incident T2DM, and age and reported family history of T2DM were tested as potential effect modifiers. Results Of the 54, 997 without T2DM at baseline, 888 reported T2DM at follow-up (cumulative incidence 1.6% over 3.4 years, annual incidence rate 0.44%). Adjusted for other risk factors, being male, older age, higher relative socio-economic disadvantage, being born in Asia, lower educational attainment, medical history of hypertension and dyslipidemia, family history of T2DM, overweight/obese, smoking, long sleeping hours, and psychological distress were significantly associated with higher odds of developing T2DM. Particularly, hypertension, dyslipidemia, and overweight/obesity were stronger predictors of T2DM among middle-aged than older adults (≥60 years). Conclusions Understanding risk factors for incident T2DM could help identify at-risk populations and develop upstream preventive strategies to combat the epidemic of diabetes.